Preliminary Psychometrics of the Participatory Evaluation and Expert Review for Classrooms Serving Students with Emotional/Behavioral Disabilities (PEER-EBD). (May 2013) - Tsai, Shu-Fei; Cheney, Douglas; Walker, Bridget
The quality of classrooms serving students with emotional and behavioral disabilities (EBD) is a continuing concern because of its influence on students' educational outcomes. Program evaluation of classrooms for students with EBD has been a recommended practice for many years since Grosenick, George, and George (1987) conducted their national study. One current approach to program evaluation has been the inclusion of classroom and school staff in a process known as participatory evaluation. The development of a program evaluation instrument, known as the Participatory Evaluation and Expert Review for Classrooms Serving Students with EBD (PEER-EBD), is reviewed in this article. This study evaluated the psychometric properties of validity and reliability for the PEER-EBD. An extensive literature review and subsequent evaluation by an expert panel established the content validity of the instrument. Data collected from 145 educators in 23 classrooms serving students with EBD revealed that the PEER-EBD has excellent internal consistency reliability. Finally, a confirmatory factor analysis supported the four-factor theoretical model of the PEER-EBD and suggested that the instrument has acceptable construct validity. These initial results suggest that the PEER-EBD has promise as a tool to help school staff self-evaluate their services, identify program strengths, and identify the areas that need further improvement.